CHOROIDAL THICKNESS IN PATIENTS WITH DIABETIC RETINOPATHY ANALYZED BY SPECTRAL-DOMAIN OPTICAL COHERENCE TOMOGRAPHY - Caio V. Regatieri; Lauren Branchini; Jill Carmody; James G. Fujimoto; Jay S. Duker (2012)
In Brief Purpose: This study was designed to examine choroidal thickness in patients with diabetes using spectral-domain optical coherence tomography. Methods: Forty-nine patients (49 eyes) with diabetes and 24 age-matched normal subjects underwent high-definition raster scanning using spectral-domain optical coherence tomography with frame enhancement software. Patients with diabetes were classified into 3 groups: 11 patients with mild or moderate nonproliferative diabetic retinopathy and no macular edema, 18 patients with nonproliferative diabetic retinopathy and diabetic macular edema, and 20 patients with treated proliferative diabetic retinopathy and no diabetic macular edema (treated proliferative diabetic retinopathy). Choroidal thickness was measured from the posterior edge of the retinal pigment epithelium to the choroid/sclera junction at 500-μm intervals up to 2,500 μm temporal and nasal to the fovea. Results: Reliable measurements of choroidal thickness were obtainable in 75.3% of eyes examined. Mean choroidal thickness showed a pattern of thinnest choroid nasally, thickening in the subfoveal region, and thinning again temporally in normal subjects and patients with diabetes. Mean subfoveal choroidal thickness was thinner in patients with diabetic macular edema (63.3 μm, 27.2%, P < 0.05) or treated proliferative diabetic retinopathy (69.6 μm, 30.0%, P < 0.01), compared with normal subjects. There was no difference between nonproliferative diabetic retinopathy and normal subjects. Conclusion: Choroidal thickness is altered in diabetes and may be related to the severity of retinopathy. Presence of diabetic macular edema is associated with a significant decrease in the choroidal thickness. A retrospective study of choroidal thickness measured by optical coherence tomography demonstrates that compared with age-matched normal subjects, the choroid is thinner in proliferative diabetic retinopathy and diabetic retinopathy with associated clinically significant macular edema.